Hypertrophic Cardiomyopathy in Youth Athletes: Successful Screening With Point‐of‐Care Ultrasound by Medical Students. (4th March 2017) - Fox, J. Christian; Lahham, Shadi; Maldonado, Graciela; Klaus, Suzi; Aish, Bassil; Sylwanowicz, Lauren V.; Yanuck, Justin; Wilson, Sean P.; Shieh, Mason; Anderson, Craig L.; English, Carter; Mayer, Ryan; et al.
Abstract : Objectives: Hypertrophic cardiomyopathy (HCM) is a life‐threatening genetic cardiovascular disease that often goes undetected in young athletes. Neither history nor physical examination are reliable to identify those at risk. The objective of this study is to determine whether minimally trained medical student volunteers can use ultrasound to screen for HCM. Methods: This was a prospective enrollment of young athletes performed at 12 area high schools and three area colleges, between May 2012 and August 2013. All participants underwent point‐of‐care ultrasound performed screening for HCM by trained medical students and reviewed by a pediatric cardiologist. An interventricular septum to left ventricular posterior wall ratio greater than 1.25 was considered to be abnormal (positive screen). Results: A total of 2332 participants were enrolled. There were 137 (5.8%) with a positive screening for HCM, of which 7 (5.1%) were confirmed to have HCM by a pediatric cardiologist. In a small cohort with positive screen for HCM, there was a 100% sensitivity (95% confidence interval, 59.04 to 100%) and 4.86% (95% confidence interval, 1.98 to 9.76%) positive predictive value of for having HCM. Conclusions: Volunteer medical students, using point‐of‐care ultrasound, were able to effectively screen for HCM in young athletes.